Association of statin use with spontaneous intracerebral hemorrhage: A cohort study. (31st July 2018) - Saliba, Walid; Rennert, Hedy S.; Barnett-Griness, Ofra; Gronich, Naomi; Molad, Jeremy; Rennert, Gad; Auriel, Eitan
Abstract : Objective: To examine the association between statin exposure in a dose-dependent manner and intracerebral hemorrhage (ICH) in a large nationwide study. Methods: The computerized database of the largest health care provider in Israel was used to identify diagnosed ICH among new users of statins, who started statin treatment between 2005 and 2010. We assessed a dose–response relationship between ICH and statins, using the average atorvastatin equivalent daily dose (AAEDD). Multivariable Cox proportional hazard regression models, adjusted for baseline disease risk score, were applied to estimate the hazard ratio of ICH. Results: Of the 345, 531 included patients, 1, 304 were diagnosed with ICH during a median follow-up of 9.5 years (interquartile range 7.6–11.0). Overall, 75.3% of patients had AAEDD <10 mg/d, 19.0% had AAEDD 0–19.9 mg/d, and 5.7% had AAEDD ≥20 mg/d. The corresponding proportions were 81.0%, 15.0%, 4.0% among ICH cases, and 75.3%, 19.0%, 5.7% among non-ICH cases. Compared to those with AAEDD <10 mg/d (reference), the adjusted hazard ratio (HR) for ICH was 0.68 (95% confidence interval [CI] 0.58–0.79) in those with AAEDD 10–19.9 mg/d, and 0.62 (0.47–0.81) in those with AAEDD ≥20 mg/d. Compared to the lowest baseline total cholesterol quartile, the adjusted HR for ICH was 0.71 (95% CI 0.62–0.82), 0.55 (0.47–0.64), and 0.57 (0.49–0.67) in those in the second, third, and highest quartiles, respectively. The results were similar and robust among highly persistent statin users and after controlling for the change in cholesterol level. Conclusions: This study confirms that the risk of ICH decreases with increasing cholesterol levels, but suggests that statin use might be associated with decreased risk of ICH.